Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1124/jpet.103.051995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 20-Hydroxyeicosatetraenoic Acid Reduce Renal Vasoconstrictor Responsiveness

Abstract: 20-Hydroxyeicosatetraenoic acid (20-HETE) is a cytochrome P450-derived constrictor eicosanoid produced by the preglomerular vasculature where it contributes to regulation of tone. Removal of the tonic inhibitory influence of nitric oxide (NO) has been reported to increase renal 20-HETE release. Because inhibition of NO synthesis enhances responses to vasoconstrictor agents, we examined a contribution for increased 20-HETE generation. In the rat kidney perfused with Krebs' buffer, responses to U46619 (9,11-dide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Endothelin-1 stimulates the formation of 20-HETE in isolated rat perfused kidney (Oyekan et al, 1997;Hercule and Oyekan, 2000;Imig et al, 2000). Quilley et al (2003) also showed that U46619, an analog of thromboxane A2 stimulated the production of 20-HETE and released 20-HETE partially act as a second messenger to cause vasoconstriction in rat perfused kidney.…”
Section: Renal Circulationmentioning
confidence: 97%
“…Endothelin-1 stimulates the formation of 20-HETE in isolated rat perfused kidney (Oyekan et al, 1997;Hercule and Oyekan, 2000;Imig et al, 2000). Quilley et al (2003) also showed that U46619, an analog of thromboxane A2 stimulated the production of 20-HETE and released 20-HETE partially act as a second messenger to cause vasoconstriction in rat perfused kidney.…”
Section: Renal Circulationmentioning
confidence: 97%
“…Inhibition of NO synthase increased efflux of 20-HETE from both Wistar and SpragueDawley kidneys with peak levels of 3.6 ng/min from SpragueDawley rats and but only 1.4 from Wistar rats (17). However, subsequent investigations suggest that the rise in 20-HETE release during isolated perfusion may have been a time-dependent phenomenon unrelated to inhibition of NO synthase (18). Sprague-Dawley alveolar macrophages produce 10 times more NO than Wistar macrophages when stimulated by lipopolysacharide (9) and NO contributes to nonadrenergic noncholinergic relaxation significantly more in Sprague-Dawley intestine than in Wistar intestine (14,15).…”
Section: Resultsmentioning
confidence: 93%
“…The greatest effect of vibration on renal blood flow (55% reduction vs. 25% reduction) occurred after infusion of phenylephrine at 1.5 ϫ 10 Ϫ7 g (infused over 30 s, at a flow rate of ϳ5 ml/min). Significantly, this is the concentration of phenylephrine (7.5 ϫ 10 Ϫ7 M), which consistently induces vasoconstriction in the isolated, perfused kidney (17,19).…”
Section: Discussionmentioning
confidence: 99%